Multifunctional Electrocatalytic Cathodes Derived from Metal–Organic Frameworks for Advanced Lithium‐Sulfur Batteries. Issue 61 (24th September 2020) - Abdelkader, Ahmed A.; Rodene, Dylan D.; Norouzi, Nazgol; Alzharani, Ahmed; Weeraratne, K. Shamara; Gupta, Ram B.; El‐Kaderi, Hani M.
Abstract: The rechargeable lithium‐sulfur (Li‐S) battery is a promising candidate for the next generation of energy storage technology, owing to the high theoretical capacity, high specific energy density, and low cost of electrode materials. The main drawbacks in the development of long‐life Li‐S batteries are capacity fading and the sluggish kinetics at the cathode caused by the polysulfides shuttle. These limitations are addressed through the design of novel nanocages containing cobalt phosphide (CoP) nanoparticles embedded in highly porous nitrogen‐doped carbon (CoP‐N‐GC) by thermal annealing of ZIF‐67 in a reductive atmosphere followed by a phosphidation step using sodium hypophosphite. The CoP nanoparticles, with large surface area and uniform homogeneous distribution within the N‐doped nanocage graphitic carbon, act as electrocatalysts to suppress the shuttle of soluble polysulfides through strong chemical interactions and catalyze the sulfur redox. As a result, the S@CoP‐N‐GC electrode delivers an extremely high specific capacity of 1410 mA h g −1 at 0.1 C (1 C=1675 mA g −1 ) with an excellent coulombic efficiency of 99.7 %. Moreover, capacity retention from 864 to 678 mA h g −1 is obtained after 460 cycles with a very low decay rate of 0.046 % per cycle at 0.5 C. Therefore, the combination of the CoP catalyst and polar conductive porous carbon effectively stabilizes the sulfur cathode, enhancing the electrochemical performance and stability of the battery. Abstract : Nanocage cathodes : MOFs‐derived multifunctional electrocatalytic cathode materials combining highly porous N‐doped carbon and CoP nanoparticles improve the performance and stability of Li‐S batteries significantly. The cathode is designed to provide polysulfides chemical entrapment and rapid redox processes by the CoP nanoparticles.